Characterisation and genetic mapping of a new X linked deafness syndrome. Issue 11 (1st November 2000) - Martin, Donna M; Probst, Frank J; Camper, Sally A; Petty, Elizabeth M
Abstract : BACKGROUND: Hereditary forms of hearing loss are classified as syndromic, when deafness is associated with other clinical features, or non-syndromic, when deafness occurs without other clinical features. Many types of syndromic deafness have been described, some of which have been mapped to specific chromosomal regions. METHODS: Here we describe a family with progressive sensorineural hearing loss, cognitive impairment, facial dysmorphism, and variable other features, transmitted by apparent X linked recessive inheritance. Haplotype analysis of PCR products spanning the X chromosome and direct sequencing of candidate genes were used to begin characterising the molecular basis of features transmitted in this family. Comparison to known syndromes involving deafness, mental retardation, facial dysmorphism, and other clinical features was performed by review of published reports and personal discussions. RESULTS: Genetic mapping places the candidate locus for this syndrome within a 48 cM region on Xq1-21. Candidate genes including COL4A5, DIAPH, and POU3F4 were excluded by clinical and molecular analyses. CONCLUSIONS: The constellation of clinical findings in this family (deafness, cognitive impairment, facial dysmorphism, variable renal and genitourinary abnormalities, and late onset pancytopenia), along with a shared haplotype on Xq1-21, suggests that this represents a new form of syndromic deafness. We discuss our findings in comparison to several other syndromic and non-syndromic deafness loci that have been mapped to the X chromosome.